2016
DOI: 10.1021/acs.jpca.6b07370
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Stabilization Effects on Ketone Autoxidation: Isomer-Specific Cyclic Ether and Ketohydroperoxide Formation in the Low-Temperature (400–625 K) Oxidation of Diethyl Ketone

Abstract: The pulsed photolytic chlorine-initiated oxidation of diethyl ketone [DEK; (CHCH)C═O], 2,2,4,4-d-DEK [d-DEK; (CHCD)C═O], and 1,1,1,5,5,5-d-DEK [d-DEK; (CDCH)C═O] is studied at 8 torr and 1-2 atm and from 400-625 K. Cl atoms produced by laser photolysis react with diethyl ketone to form either primary (3-pentan-on-1-yl, R) or secondary (3-pentan-on-2-yl, R) radicals, which in turn react with O. Multiplexed time-of-flight mass spectrometry, coupled to either a hydrogen discharge lamp or tunable synchrotron photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…To obtain preliminary data for the reaction mechanism study, some additional reactions were conducted according to Scheme 3. The kinetic deuterium isotope effects [14] observed in the control experiments (k H /k D = 3.9) were consistent with the C-H cleavage, being the rate-limiting step (see Supplementary Materials). We also did the two controlled experiments (Scheme 4).…”
Section: Discussionsupporting
confidence: 76%
“…To obtain preliminary data for the reaction mechanism study, some additional reactions were conducted according to Scheme 3. The kinetic deuterium isotope effects [14] observed in the control experiments (k H /k D = 3.9) were consistent with the C-H cleavage, being the rate-limiting step (see Supplementary Materials). We also did the two controlled experiments (Scheme 4).…”
Section: Discussionsupporting
confidence: 76%
“…The high-pressure experiments, conducted with ∼50–500 higher oxygen partial pressure than at 10 Torr, lead to much higher rate coefficients for O 2 addition and much more efficient collisional relaxation of chemically activated radicals. Our previous work on alkane, ether, and ketone oxidation revealed that high- P , high-oxygen conditions in the HPR enhance second-O 2 addition relative to the LPR. ,, We therefore assigned the m / z = 67, 84, 100, and 116 peaks at 3000 and 7500 Torr to species formed by γ-QOOH + O 2 , as shown in Figure . In addition, the time dependence of m / z = 57 and 82 peaks (marked with asterisks in Figure ) suggests that they are also likely due to DI fragments of second-O 2 addition products; however, we could not definitively assign them.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Participation of the OH group with the delocalized π electrons may further stabilize the radical. RSRs play a significant chemical role in oxygen-rich gas-phase environments (e.g., interstellar medium, planetary atmospheres, and combustion) , due to their resistance to oxidation by molecular oxygen. Reaction of an RSR with O 2 forms a peroxy radical at the expense of localizing the previously delocalized electron, leading to a weak C–O 2 bond.…”
Section: Introductionmentioning
confidence: 99%